Pengaruh Gaya Kepemimpinan Transformasi dan Motivasi Kerja Terhadap Kinerja Karyawan pada Perusahaan Agribisnis LQ45: Stufi Kasus PT. Astra Agro Lestari.Tbk - Mere, Klemens (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The current economic climate is experiencing rapid growth, prompting companies to compete in enhancing their services to attract and retain consumers. The role of human resources as a key driver in companies becomes increasingly crucial, where leadership style and work motivation play significant roles in optimizing employee performance. This study aims to identify the impact of transformational leadership style and work motivation on employee performance at agribusiness companies listed in LQ45, specifically PT. Astra Agro Lestari Tbk, both simultaneously and partially, and to determine which variable has a dominant effect between the two. This research employs an explanatory research approach with a survey method, where data are collected through questionnaires, interviews, literature reviews, and documentation. The sample consists of 40 respondents, and data analysis is conducted using multiple linear regression. The findings indicate that: (1) Transformational Leadership Style (X1) has a t-value of 0.319, which exceeds the t-table value of 0.279, with a significance value of 0.00, which is less than α= 0.05, demonstrating that transformational leadership style has a significant impact on employee performance at PT. Astra Agro Lestari Tbk; (2) Work Motivation (X2) has a t-value of 1.615, which is greater than the t-table value of 0.279, with a significance value of 0.002, also less than α= 0.05, indicating that work motivation significantly affects employee performance; (3) The analysis reveals an F-value of 112.362 with a probability of 0.000, which is below 0.05, indicating that both transformational leadership style and work motivation simultaneously have a significant effect on employee performance.